Internal herniation of sigmoid colon into ladd's band - Praveen, CR; Patowary, BN; Kumar, S; Shrestha, P (Journal of College of Medical Sciences-Nepal, 2012)
Ladd's bands are generally known to cause duodenal and small bowel obstruction. Sigmoid colon compression by Ladd's bands has not been reported till now though a few cases of colonic obstruction have been reported. We report a case of sigmoid colon obstruction secondary to its herniation into Ladd's band in a child with intestinal malrotation. DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6710 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 53-55